Prototype to measure the total harmonic distortion - Valderrama, David Mauricio; Hernández, Oscar (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
It shows the design of data acquisition circuits and conditioning for the current and voltage signals of a monophase electric network like the basic components of a portable prototype for measurement of total harmonic distortion (THD) in the net, in the same way, it ilustrates the design of the software for processing of the acquired programmed in visual C# and Matlab 7.4.